A novel acquisition method for nuclear spectra based on pulse area analysis*Supported by National Natural Science Foundation of China (11375077, 11027508). (April 2015) - Li 李, Dong-Cang 东仓; Ren 任, Zhong-Guo 忠国; Yang 杨, Lei 磊; Qi 祁, Zhong 中; Meng 孟, Xiang-Ting 祥厅; Hu 胡, Bi-Tao 碧涛
Abstract: A novel simple method based on pulse area analysis (PAA) is presented for acquisition of nuclear spectra by a digitizer. The PAA method can be used as a substitute for the traditional method of pulse height analysis (PHA). In the PAA method a commercial digitizer was employed to sample and sum in the pulse, and the area of the pulse is proportional to the energy of the detected radiation. The results of simulation and experiment indicate the great advantages of the PAA method, especially as the count rate is high and the shaping time constant is small. When the shaping time constant is 0.5 μs, the energy resolution of PAA is about 66% better than that of PHA.